2004
DOI: 10.1080/02652040310001637820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the permeability characteristics of different polymethacrylates on the pharmaceutical characteristics of verapamil hyhdrochloride-loaded microspheres

Abstract: Microspheres containing verapamil hydrochloride (VRP) were prepared with various polymethacrylates, with different permeability characteristics (Eudragit RS 100, Eudragit RL 100, Eudragit L 100 and Eudragit L 100-55) and also with mixtures of these polymers in a 1:1 ratio using the solvent evaporation method. The aim was to investigate the effects of the permeability of the polymers on drug release rates and the characteristics of the microspheres. To achieve these aims, yield, incorporation efficiency, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…The same method but in acetone:MeOH solutions was proposed for preparing verapamil-containing microspheres consisting of combinations of Eudragit ® RS100 with L100 or L100-55 in a 1:1 mass ratio [26]. Interesting trends were found by analyzing the viscosities of the disperse media and determining the particle sizes of the combined disperse phases.…”
Section: Preparation Of Microspheres and Micropelletsmentioning
confidence: 98%
“…The same method but in acetone:MeOH solutions was proposed for preparing verapamil-containing microspheres consisting of combinations of Eudragit ® RS100 with L100 or L100-55 in a 1:1 mass ratio [26]. Interesting trends were found by analyzing the viscosities of the disperse media and determining the particle sizes of the combined disperse phases.…”
Section: Preparation Of Microspheres and Micropelletsmentioning
confidence: 98%
“…Moreover, solid dispersions (coprecipitates) of different drugs and countercharged poly(meth)acrylates are successfully used in matrix tablets production {RLPO(RSPO)/S100[L100, Eudragit R L 100-55 (L100-55)]}, 8 (E100/S100). 9,10 Microspheres prepared by a solvent evaporation method with the copolymer combinations (RL100/L100-55), 11 [RS100/L100(L100-55)] 12 showed a stronger sustained release.…”
Section: Introductionmentioning
confidence: 99%
“…Pignatello et al (34) showed that the drug release from Eudragit RL100 particles was complex in nature which involves the occurrence of dissolutive and diffusive phenomena. Overall the drug release rate was faster which were probably due to the high water permeability and swellability characteristics of Eudragit RL 100 (51). The presence of a high content of quaternary ammonium groups makes the polymer more permeable to water.…”
Section: Discussionmentioning
confidence: 84%